Efficient Biosynthesis of Fungal Polyketides Containing the Dioxabicyclo-octane Ring System - Mao, Xu-Ming (J Am Chem Soc, 2015)
Aurovertins are fungal polyketides that exhibit potent inhibition of ATP synthase. Aurovertins contain a 2,6-dioxabicyclo[3.2.1]-octane ring that is proposed to be derived from a polyene precursor through regioselective oxidations and epoxide openings. In this study, we identified only four enzymes are required to produce aurovertin E 4. The core polyketide synthase produces a polyene α-pyrone 10. Following pyrone O-methylation by a methyltransferase, a flavin-dependent monooxygenase (FMO) and an epoxide hydrolase can iteratively transform the terminal triene portion of the precursor into the dioxabicyclo[3.2.1]-octane scaffold. We demonstrate that a tetrahydrofuranyl polyene 12 is the first stable intermediate in the transformation, which can undergo epoxidation and anti-Baldwin 6-endo-tet ring opening to yield the cyclic ether product. Our results further demonstrate the highly concise and efficient ways in which fungal biosynthetic pathways can generate complex natural product scaffolds.